Calculation of Air Conditioning Cooling Load on 1st Floor of Class III Inpatient Building at X Hospital - Suryaman, Nia Nuraeni; Santoso, Heru (CENTRAL ASIA AND THE CAUCASUS, 2022)
Air conditioning in a building is needed to provide environmental comfort in terms of thermal for each occupant. Air conditioning also serves to maintain and protect equipment or machinery in a building, building or factory. The building consists of rooms that have their respective functions. Then there should be a system for regulating air temperature, ventilation and others for each group of rooms according to their needs. The condition of a building is influenced by external conditions and is also influenced by additional heat (heat gain) from inside the room, so that each room has a load that requires cooling. The purpose of this research is to regulate the temperature and humidity of the air at MCC Building Architectural GA according to their respective functions and to calculate the cooling load of the room at MCC Building Architectural GA. The results of this study are the total cooling load for the air conditioning system for GSH 129774.2 Watt, GLH 12946.89 Watt and GTH 142721.09 Watt.